2011
DOI: 10.3390/molecules16075769
|View full text |Cite
|
Sign up to set email alerts
|

Use of Novel Cardanol-Porphyrin Hybrids and Their TiO2-Based Composites for the Photodegradation of 4-Nitrophenol in Water

Abstract: Cardanol, a well known hazardous byproduct of the cashew industry, has been used as starting material for the synthesis of useful differently substituted “cardanol-based” porphyrins and their zinc(II), copper(II), cobalt(II) and Fe(III) complexes. Novel composites prepared by impregnation of polycrystalline TiO2 powder with an opportune amount of “cardanol-based” porphyrins, which act as sensitizers for the improvement of the photo-catalytic activity of the bare TiO2, have been used in the photodegradation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The porphyrins are brown-red sticky solids, very soluble in CHCl 3 or CH 2 Cl 2 [32]. This substituted cardanolbased porphyrin and their metallic complexes have been used extensively in photo degradation of toxic, bio-refractory 4-nitro phenol in water, which is dangerous for the ecosystem and for human health [32]. CNSL is also useful in fuel blends and fuel mixtures [33] and for producing diesel oil [34].…”
Section: Cnsl As Petrochemical Feedstockmentioning
confidence: 99%
“…The porphyrins are brown-red sticky solids, very soluble in CHCl 3 or CH 2 Cl 2 [32]. This substituted cardanolbased porphyrin and their metallic complexes have been used extensively in photo degradation of toxic, bio-refractory 4-nitro phenol in water, which is dangerous for the ecosystem and for human health [32]. CNSL is also useful in fuel blends and fuel mixtures [33] and for producing diesel oil [34].…”
Section: Cnsl As Petrochemical Feedstockmentioning
confidence: 99%
“…The synthesis of porphyrins starting from cardanol are mentioned by many papers since 2004, [26][27][28][29] and they employed a procedure which consists in producing an aldehyde derivative as precursor. Normally, this precursor is compound 3 (4-[2-(3-pentadecylphenoxy) ethoxy] benzaldehyde), obtained by a reaction between compound 2 (1-(2-bromoethoxy)-3-pentadecylbenzene) and 4-hydroxybenzaldehyde in acetone using anhydrous potassium carbonate (K 2 CO 3 ) as base, stirred for 24 h and with 40% yield.…”
Section: Synthesismentioning
confidence: 99%
“…Cardanol (CDN) is the major by-product from cashew-nut processing and arising from the thermal decomposition of anacardic acid [7][8][9]. It is indeed a mixture of both Z and E isomers of one long alkyl-chain attached to the phenolic ring, which differs in the unsaturation degree [10] (see Figure 1).…”
Section: Introductionmentioning
confidence: 98%
“…However, the industrial production also generates a massive amount of caustic, viscous and harmful residues, containing a mixture of saturated and unsaturated meta-alkylphenols with strong amphiphilic character [6][7][8]. The high stability [7] and toxicity [9] of these compounds represent a threat to the environment if the wastewaters containing them do not receive a suitable pre-treatment before the final disposal. Biological treatment is the most employed around the world for this kind of effluents, however, several studies have showed that it is inefficient to remove recalcitrant organic compounds [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation